35.3k views
4 votes
P

p 2 - 4p - 12

User Jfrmilner
by
7.4k points

2 Answers

3 votes

Answer:

(p - 6)(p + 2).

Explanation:

Factoring p² - 4p - 12.

Note that -6 * 2 = -12 and -6 + 2 = -4 so the answer is:-

(p - 6)(p + 2).

User Tatarin
by
7.6k points
7 votes

Answer:

(p - 6)(p + 2)

Explanation:

consider the product of the factors of the constant term which sum to give the coefficient of the p- term

product = - 12 and sum = - 4

The factors are - 6 and + 2

p² - 4p - 12 = (p - 6)(p + 2)


User Dhu
by
6.9k points